The effect of higher capital requirements on bank lending: The capital surplus matters - Dominika Kolcunová; Simona Malovaná (Charles University in Prague, Institute of Economic Studies (IES), 2019)
This paper studies the impact of higher additional capital requirements on loan growth to private sector of banks in the Czech Republic. The empirical results indicate that there is a negative effect of higher additional capital requirements on loan growth of banks with relatively low capital surplus. In addition, the results confirm that the relationship between capital surplus and loan growth is important also in the period of stable capital requirements, i.e. it does not serve only as an intermediate channel of higher additional capital requirements.
Keywords: C22; E32; G21; G28; 330; Bank lending; banks' capital surplus; regulatory capital requirements